2021
DOI: 10.1108/ijqrm-02-2021-0039
|View full text |Cite
|
Sign up to set email alerts
|

Developing a hybrid software reliability growth model

Abstract: PurposeThe purpose of this paper is to develop a new software reliability growth model considering different fault distribution function before and after the change point.Design/methodology/approachIn this paper, the authors have developed a framework to incorporate change-point in developing a hybrid software reliability growth model by considering different distribution functions before and after the change point.FindingsNumerical illustration suggests that the proposed model gives better results in comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…OSS reliability tools have been compared and reviewed and the characteristics and applications have been summarized 52 . More work in multi‐release modelling of OSS has been put forth by the number of researchers 13‐21,23‐29,34,38,40,42,48 …”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…OSS reliability tools have been compared and reviewed and the characteristics and applications have been summarized 52 . More work in multi‐release modelling of OSS has been put forth by the number of researchers 13‐21,23‐29,34,38,40,42,48 …”
Section: Literature Reviewmentioning
confidence: 99%
“…52 More work in multi-release modelling of OSS has been put forth by the number of researchers. [13][14][15][16][17][18][19][20][21][23][24][25][26][27][28][29]34,38,40,42,48 Following research gaps have been observed in the literature:…”
Section: Literature Reviewmentioning
confidence: 99%
“…The parameters of the model are determined based on real data, and the parameters are substituted into a reliability formula. Many models of reliability have been introduced in the past few decades [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%